SIMULASI OPTIMALISASI JADWAL KEBERANGKATAN KAPAL FERRY DENGAN METODE MONTE CARLO (STUDI KASUS DI PELABUHAN INTERNATIONAL SEKUPANG BATAM) - siringo, Anggiat marubah (Journal Information System Development (ISD), 2017)
Monte carlo methods can be used to find a mathematical solution which can comprise many variables that are difficult to solve. Monte Carlo is the basis for all of the algorithms of simulation method which is based on the thinking problems to solve to get better results by giving as much value to obtain a higher accuracy. Monte Carlo method, one of the most appropriate method to conduct research in the port of Batam Sekupang interasional to optimize scheduling ferry. A good schedule will make operating costs more economical. Given this study the authors expect will help service providers sea transportation in this case the Port International Sekupang Batam in determining the scheduled departure ferries which have been designed in sisitem application programming language PHP, so the operating costs of departure ferry services more economically and benefits of cost passengers more leverage, so that companies can survive in the welfare of employees